Pembuatan Video Panduan Layanan Perpustakaan di Perpustakaan Universitas Negeri Padang - Rossalyna, Elsha; Ardoni, Ardoni (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2017)
The purpose of this paper is to describe the making of library service guide video in the Library of Padang State University to make it easier to find an information needed. The method was a qualitative method with data collection techniques through direct observation and interview. There are three stages in the video production: First, Preproduction is an early stage before the implementation of video production. This steps are very important for video production because this stage is all the planning steps for video production is done. In this pre-production stage was done: search and discovery of ideas, making synopsis, treatment, sroryboard, shotting script, production planning, and production preparation. Second, Production, video production stage is the stage to realize all the steps that exist in preproduction stage. At the production stage, the video production team is usually led by a director who has a role to take responsibility for the ongoing running of video production. Usually the director assisted by several assistants to assist in ongoing video production. Third, Postproduction is the final stage in video production before the video is ready to be presented or distributed. In this post-production process were required video editing software and adequate tools to perform video editing process.Keyword: library, production, video.